Pengaruh Penggunaan Media Video Pembelajaran dengan Pendekatan Saintifik Terhadap Sikap Ilmiah dan Hasil Belajar Kognitif Siswa Kelas IV - Dela Safitri; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
This study aims to determine the effect of using video learning media with a scientific approach on scientific attitudes and cognitive learning outcomes in fourth grade students. This research is a quantitative research, with a Quasi Experimental Design approach. Experimental Design has a control group but does not fully function in controlling external variables that affect the implementation of the experiment. The population in this study were all fourth grade students at SDN 78 Bengkulu Selatan. The sample in this study was 15 students in class IVA as the experimental class and 15 students in class IVB as the control class. The instruments given are in the form of questionnaires and questions consisting of variables of scientific attitude and cognitive learning outcomes. The results of this study indicate that there is a significant effect of learning videos with a scientific approach on scientific attitudes and cognitive learning outcomes of fourth grade students.